ANALISIS KEBUTUHAN PENGEMBANGAN MEDIA E-COMIC TENTANG MATERI ALJABAR UNTUK SISWA KELAS III SEKOLAH DASAR - Isni Rahmadiani; Karlimah, Ika Fitri Apriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to analyze the need for the development of E-Comic media on algebra material for third-grade elementary school students at SDN 1 Waringinsari, Banjar City, West Java. This research is motivated by the limited availability of learning media, particularly for algebra material, as well as the lack of learning tools that support the needs of Generation Alpha students, who are generally familiar with digital technology. Therefore, innovative learning media that align with their characteristics and interests are needed. This study employs a qualitative method with a descriptive design. Data collection techniques include interviews with teachers and students, document studies, and observations, which were then analyzed using the Miles and Huberman model. The research results show that there is no digital media or E-Comic available to support algebra learning. In addition, teachers expressed the need for innovative media to help students understand algebraic concepts, while students showed interest in visually engaging comics that are relevant to their daily lives.